Phosphate removal from aqueous solution using coir-pith activated carbon - Kumar P.; Sudha S.; Chand S.; Srivastava V.C. (My University, 2025)
The present study deals with the removal of phosphates from aqueous solution using activated carbon developed from coir pith. Batch adsorption experiments were performed to delineate the effect of initial pH, contact time, adsorbent dose and temperature on the removal of phosphates by coir-pith activated carbon (CAC) (activated by H2SO4). The removal was found to be maximum in the pH range of 6-10. The kinetics of adsorption showed that the phosphate adsorption onto CAC was a gradual process with a quasi-equilibrium being attained in 3 h. The adsorption equilibrium data followed the Temkin isotherm. Thermodynamic parameters such as ΔG°, ΔH°, and ΔS° were evaluated by applying the Arrhenius and van't Hoff equations, and it was found that the adsorption of phosphate on CAC was spontaneous and endothermic. © Taylor & Francis Group, LLC.